Ambient electrocatalytic N2 reduction to NH3 by metal fluorides. Issue 30 (16th July 2019) - Li, Peipei; Liu, Zaichun; Wu, Tongwei; Zhang, Ya; Wang, Linyu; Wang, Li; Ji, Lei; Zhang, Youyu; Luo, Yonglan; Wang, Ting; Liu, Shanhu; Wu, Yuping; et al.
Abstract : LaF3 nanoplates are efficient for electrocatalytic N2 reduction in 0.5 M LiClO4 with a high faradaic efficiency of 16.0% and a large NH3 yield of 55.9 μg h −1 mgcat. −1 . Abstract : The high-temperature and high-pressure Haber–Bosch process for industrial NH3 production is rather energy-intensive with heavy CO2 emission. Electrochemical N2 reduction in aqueous media offers an eco-friendly and sustainable alternative to ambient NH3 synthesis with the aid of efficient electrocatalysts for the N2 reduction reaction (NRR), but they suffer from limited current efficiency for NH3 formation due to the unavoidable competing hydrogen evolution reaction (HER). Here, we report that LaF3 nanoplates act as a superb NRR electrocatalyst for ambient N2 -to-NH3 fixation with excellent selectivity due to their effective inhibition of the HER and activation of the NN triple bond. In 0.5 M LiClO4, they achieve a high faradaic efficiency of 16.0% and a large NH3 yield of 55.9 μg h −1 mgcat. −1 at −0.45 V vs. the reversible hydrogen electrode, much higher than those of La2 O3 (1.4%; 12.5 μg h −1 mgcat. −1 ) and most reported aqueous-based NRR catalysts. This catalyst also shows high long-term electrochemical and structural stability. The detailed NRR mechanism is also discussed.